Ureaplasma species modulate cell adhesion molecules and growth factors in human brain microvascular endothelial cells. (September 2019) - Silwedel, Christine; Speer, Christian P.; Haarmann, Axel; Fehrholz, Markus; Claus, Heike; Schlegel, Nicolas; Glaser, Kirsten
Highlights: Ureaplasma spp. modulate cell adhesion molecule responses in HBMEC. Ureaplasma spp. modulate growth factor responses in HBMEC. Ureaplasma spp. seem to compromise blood-brain barrier integrity. Ureaplasma spp. may have an immunomodulatory capacity in co-infections. Ureaplasma spp. are clinically relevant pathogens. Abstract: Ureaplasma species (spp.) are considered commensals of the adult urogenital tract, but may cause chorioamnionitis and preterm birth as well as sepsis and meningitis in neonates. Pathomechanisms in Ureaplasma -driven neuroinflammation are largely unknown. This study addressed mRNA and protein expression of intercellular and vascular cell adhesion molecules (ICAM-1, VCAM-1), granulocyte-colony stimulating factor (G-CSF), and vascular endothelial growth factor (VEGF) in native or lipopolysaccharide (LPS) co-stimulated human brain microvascular endothelial cells (HBMEC) exposed to Ureaplasma (U.) urealyticum or U. parvum . Ureaplasma spp. reduced G-CSF mRNA ( p  < 0.05) and protein expression ( p  < 0.01) and increased VEGF mRNA levels ( p  < 0.01) in native HBMEC. Upon co-stimulation, Ureaplasma isolates enhanced LPS-evoked VEGF and ICAM-1 mRNA expression ( p  < 0.05), but mitigated G-CSF and VCAM-1 mRNA responses ( p  < 0.05). In line with previous findings, our results indicate an ability of Ureaplasma spp. to compromise blood-brain barrier integrity, mitigate immune defense, and subdue neuroprotective mechanisms. This may facilitate intracerebral inflammation, allow chronic infections, and promote brain injury. More pronounced effects in co-stimulated cells may indicate an immunomodulatory capacity of Ureaplasma spp.